Cyclodextrin-engineered bioinspired nanozyme microneedle for adaptive theranostic regulation of hyperuricemia and gout - Xu-Wei Qi; Hua-Zhou Niu; Ya-Hui Chen; Ye-Tao Zhang; Jing Li; Zu-E Hu; Jia-Xin Wang; Yi-Qi Liu; Bang-Jing Li; Sheng Zhang (Carbohydrate Polymers, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Prioritizing climate action maximizes synergies among global environmental SDGs: A causal network analysis - Yizhong Huan; Fei Wu; Xiaoyun Li; Jing Wang; Yiming Su; Yang Lan; Feng Kong; Jixi Gao; Wenwu Zhao; Lingqing Wang; Jian Hu; Wenjie Zhao; et al. (Applied Geography, 2026)

Biphasic synergistic enhancement hydrogels via modulus-matched rubbery and entangled phases - Jing Duan; Yuyi Zhang; Shixiang Zhao; Yuri V. Petrov; Vladimir E. Baulin; Aslan Yu Tsivadze; Dechang Jia; Yu Zhou; Baoqiang Li (Chemical Engineering Journal, 2026)

Two episodes of Gzhelian (latest Carboniferous) volcanism immediately predate Asselian (early Permian) cooling and glaciation - Ye Wang; Jing Lu; Minfang Yang; Pam Vervoort; Kai Zhou; Joyce A. Yager; Sarah E. Greene; Ruoyu Sun; Yuchen Yang; Shifeng Dai; Longyi Shao; Jason Hilton (Global and Planetary Change, 2026)

Repeated pulses of volcanism drove the Late Triassic Carnian Pluvial episode - Peixin Zhang; Minfang Yang; Jing Lu; Jacopo Dal Corso; Zhongfeng Jiang; Shifeng Dai; Lei Wang; Kai Zhou; Xiaotao Xu; Yanghang Guo; Huijuan Chen; Longyi Shao; et al. (Global and Planetary Change, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Transcriptomic Analysis Under Drought and Salt Stress Provides Insight into Genes Putatively Involved in Ginsenoside Biosynthesis in Panax japonicus Meyer - Jiangbo Zhou; Jing Li; E. Liang; Minjie Qi; Yuanshe Huang; Lai Zhang (Biochemical Genetics, 2025)

The molecular mechanism of electrical stimulation on enhancing the foaming properties of egg white liquid - E. Zhao; Chan Li; Jing Yuan; Keshan Wang; Jingchun Ma; Ying Zhou; Qiujin Zhu; Xiaoli Liu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Exposure to particulate matter may affect semen quality via trace metals: Evidence from a retrospective cohort study on fertile males - Yuting Cheng; Jiaqi Zhu; Qiuqin Tang; Jing Wang; Jialin Feng; Yijie Zhou; Jinhui Li; Feng Pan; Xiumei Han; Chuncheng Lu; Xinru Wang; Marvin E. Langston; et al. (Chemosphere, 2024)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Insights into the pigment and non-pigment phenolic profile of polyphenol extracts of jujube peel and their antioxidant and lipid-lowering activities - Jin-Feng Dou; Cai-E Wu; Gong-Jian Fan; Ting-Ting Li; Xiao-Jing Li; Dan-Dan Zhou; Jin-Peng Zhu; Chun-Mei Li (Food Bioscience, 2023)

Handelin extends lifespan and healthspan of Caenorhabditis elegans by reducing ROS generation and improving motor function - Huijie Zhang; Jiawei Qin; Xinqiang Lan; Weirong Zeng; Jing Zhou; Tian-E Huang; Wan-Li Xiao; Qi-Quan Wang; Sujiao Sun; Weiting Su; Wenhui Nie; Shan Yang; et al. (Biogerontology, 2022)

Efficiency comparison of B6(Cg)-Tyrc−2j /J and C57BL/6NTac embryos as hosts for the generation of knockout mice - Yu’e Ma; Lei He; Lijie Xiang; Jie Zhang; Jing Wang; Wenjing Zhu; Wenni Cao; Yichen Zhu; Man Gao; Fei Zhou; Zhiwei Liu (Transgenic Research, 2021)
Careful selection of the host embryo is critical to the efficient production of knockout (KO) mice when injecting mouse embryonic stem (mES) cells into blastocysts. B6(Cg)-Tyr c−2j /J (B6 albino) and C57BL/6NTac (B6NTac) strains of mice are widely used to produce host blastocysts for such procedures. Here, we tested these two strains to identify an appropriate match for modified agouti C57BL/6N (JM8A3.N1) mES cells. When comparing blastocyst yield, super-ovulated B6NTac mice produced more injectable blastocysts per female than B6 albino mice (8.2 vs. 5.4). There was no significant difference in birth rate when injected embryos were transferred to the same pseudopregnant recipient strain. However, the live birth rate was significantly higher for B6NTac blastocysts than B6 albino blastocysts (62.7% vs. 50.2%). In addition, the proportion of pups exhibiting high-level and complete chimerism, as identified by coat color, was also significantly higher in the B6NTac strain. There was no obvious difference in the efficiency of germline transmission (GLT) when compared between B6NTac and B6 albino host embryos (61.5% vs. 63.3% for mES clones; 64.5% vs. 67.9% for genes, respectively), thus suggesting that an equivalent GLT rate could be obtained with only a few blastocyst injections for B6NTac embryos. In conclusion, our data indicate that B6NTac blastocysts are a better choice for the microinjection of JM8A3.N1 mES cells than B6 albino blastocysts.

A Photopolymerized Semi-Interpenetrating Polymer Networks-Based Hydrogel Incorporated with Nanoparticle for Local Chemotherapy of Tumors - Yeying Wang; Qilong Li; Jing-e Zhou; Jingwen Tan; Minghao Li; Nan Xu; Feng Qu; Jian Chen; Ji Li; Jing Wang; Zhiqiang Liang; Lei Yu; et al. (Pharmaceutical Research, 2021)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Soybean vein necrosis orthotospovirus can move systemically in soybean in the presence of bean pod mottle virus - Jing Zhou; Ioannis E. Tzanetakis (Virus Genes, 2020)

Variability in herbivore-induced defence signalling across different maize genotypes impacts significantly on natural enemy foraging behaviour - Mirian F. F. Michereff; Diego M. Magalhães; Marla J. Hassemer; Raúl A. Laumann; Jing-Jiang Zhou; Paulo E. de A. Ribeiro; Paulo A. Viana; Paulo E. de O. Guimarães; Pedro H. C. Schimmelpfeng; Miguel Borges; John A. Pickett; Michael A. Birkett; et al. (Journal of Pest Science, 2019)

Soybean vein necrosis virus: an emerging virus in North America - Jing Zhou; Ioannis E. Tzanetakis (Virus Genes, 2019)

Biosynthesis of staphylococcal enterotoxin A by genetic engineering technology and determination of staphylococcal enterotoxin A in water by HPLC-ESI-TOF - Hong-na Li; Fei Yuan; Yun-jing Luo; Jian-feng Wang; Chuan-bin Zhang; Wei-e Zhou; Zhi-qin Ren; Wen-jie Wu; Feng Zhang (Environmental Science and Pollution Research, 2017)

Antibacterial mechanism of high-mobility group nucleosomal-binding domain 2 on the Gram-negative bacteria Escherichia coli - Heng Li; Xiao-fei Shen; Xin-e Zhou; Yan-e Shi; Lu-xia Deng; Yi Ma; Xiao-ying Wang; Jing-yu Li; Ning Huang (Journal of Zhejiang University-SCIENCE B, 2017)

Multiscale Modeling in the Clinic: Drug Design and Development - Colleen E. Clancy; Gary An; William R. Cannon; Yaling Liu; Elebeoba E. May; Peter Ortoleva; Aleksander S. Popel; James P. Sluka; Jing Su; Paolo Vicini; Xiaobo Zhou; David M. Eckmann (Annals of Biomedical Engineering, 2016)

Diodia vein chlorosis virus is a group-1 crinivirus - Ioannis E. Tzanetakis; William M. Wintermantel; Bindu Poudel; Jing Zhou (Archives of Virology, 2011)

Erratum to: Incidence rates of exocrine and endocrine pancreatic cancers in the United States - Jing Zhou; Lindsey Enewold; Alexander Stojadinovic; Guy T. Clifton; John F. Potter; George E. Peoples; Kangmin Zhu (Cancer Causes & Control, 2011)

Incidence rates of exocrine and endocrine pancreatic cancers in the United States - Jing Zhou; Lindsey Enewold; Alexander Stojadinovic; Guy T. Clifton; John F. Potter; George E. Peoples; Kangmin Zhu (Cancer Causes & Control, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)